Design of functionalized polysiloxanes: synthesis and study on sulfur-containing xerogels with mono- and bifunctional surface layer - Zub, Yu.L.; Melnyk, I.V.; Chuiko, A.A.; Cauzzi, D.; Predieri, G. (Поверхность, 2002)
Urea- and thiourea-containing trialkoxysilanes were prepared with a high yield and purity. By sol-gel processing of these precursors the new functionalized xerogels were synthesized and characterized by FTIR, elemental analysis, thermal analysis and adsorption method. Mono- and bifunctionalized xerogels were easily prepared by mixing of precursors in the desired ratios together with tetraethyl orthosilicate. Obtained functional polysiloxanes are perspective materials for metal sorption and hybrid catalysis applications.